O contexto escolar e a educação de estudante autista: reflexões à luz da perspectiva histórico cultural - Braunstein, Valeria Campinas [UNIFESP] (2020)
This work presents an investigation about the organization of a public school located in a small city of the state of São Paulo, for the participation of students with autism. In this context, were considered the singularities that characterize the development of these students, the school infrastructure in human and material resources, the support of services, the interactions and the pedagogical practices of the everyday school life. The study is based on Vigotski's cultural- historical psychology, which highlights the social dimension of learning and development processes in the existence of disabilities and the importance of school education in these processes. The data was built from observation of a second year student with autism from a public school for one year, with follow-up twice a week in the first semester and six meetings in the second semester, as well the study of documents and open interviews with school professionals and technical team linked to the education and family secretary. The objective was to know, explain and analyze, in the current historical-political-pedagogical context, the impact of the conditions and modes of school organization on the emergence of possibilities of school inclusion of these students. The analyses were organized into four categories: 1) Structure and functioning of the school, approaching the school infrastructure in human resources, architectural and material; 2) Pedagogical practices proposed by teachers; 3) Interaction, about the relations between family, professionals and among children; and 4) Educational support and network services approaching the support among professionals and the interdisciplinary in the support to the teachers for the development of the student with autism. The results of the research allowed a broader understanding about the subject, indicating that although an educational practice based on the principles of inclusive education is prescribed and provided for in national and municipal legislation in the school's political pedagogical project, this does not happen in their daily lives due to disruptions in the organization of school routine. The shortage of employees in the school unit generates discontinuity in the teaching work, in the attendance of autistic students, and in the routine of the management team, which finds itself having to reorder the administrative work abdicating some of its functions. There is an insufficient number of education and health technicians at the school's disposal, due to the demand of students with disabilities, which results in a fragmented, unstable and disorganized with interdisciplinary support, guidance and training the school's professionals. In the network services there is no dialogue between professionals and educators. Thus, consequently, the learning responsibility process of these students relies with the teacher, who, depending on his belief about the possibilities of the student, can pathologize and blame him for failure in schooling or collaborate with his development by finding resources their own differentiated working strategies. Despite the possibility of identifying mediating processes that triggered significant interactions within the school, it is concluded that the structural disorganization of the school impairs its functioning, which has repercussions on a characteristically disaggregated, unpredictable and discontinuous attendance to students with autism. This, based on clandestine adjustments between what is allowed and what is not allowed, compromises its learning and development.